[PP.21.11] NOVEL IDENTIFICATION OF NOCTURNAL HYPERTENSION IMPROVES PREDICTION OF CARDIOVASCULAR DEATH IN A GENERAL POPULATION. (September 2017) - Head, G.; Sata, Y.; Imai, Y.; Ohkubo, T.; Kikuya, M.; Schlaich, M.
Abstract : Objective: Subjects with nocturnal hypertension often show a non-dipping pattern and have higher risk of cardiovascular mortality. Usually, time-based classification of nocturnal dipping is used to define risks but this is limited by a variability of dipping pattern amongst subjects (e.g. early risers and late risers). Design and method: We applied new method to classify non-dipper using a 6 parameter logistic equation to determine the exact magnitude of the dip irrespective of time, and defined as the range of mean blood pressure (BP) between the upper and lower plateaus. We examined the prognostic value of a < 10% reduction in range versus the conventional day-night difference of <10% using the data from the Ohasama 15-year outcome study. Results: Among 1522 subjects, 7.4% (n = 112) was categorized non-dipper by our new range classification (R-ND), they had higher nocturnal mean BP (89 ± 10 vs 84 ± 9 mmHg, p < 0.01), lower day-time mean BP (88 ± 10 vs 93 ± 10 mmHg, p < 0.01), similar 24 h averaged mean BP (88 ± 10 vs 89 ± 9 mmHg), and were older (67.1 ± 11 vs 61.3 ± 11, p < 0.01), compared with dippers. On the other hand, using convention classification by times, 56% (n = 847) defined as non-dippers (C-ND), had higher nocturnal mean BP (87 ± 10 vs 81 ± 7 mmHg, p < 0.01), lower day-time mean BP (90.1 ± 9.6 vs 95.0 ± 9.2 mmHg, p < 0.01), similar 24 h averaged mean BP (88.6 ± 9.4 vs 88.8 ± 8.2 mmHg), and were older (63.5 ± 0.4 vs 59.5 ± 0.4, p < 0.01), compared with dippers. Both R-ND and C-ND were correlated with the severe adverse cardiovascular events but R-ND predicted all caused deaths (odds ratio 2.72, p < 0.01) and cardiovascular deaths (odds ratio 2.33, p < 0.01) stronger than C-ND (odds ratio 2.2, p < 0.01; odds ratio 1.91, p < 0.01, respectively). Conclusions: In conclusion, our novel methods of analysis avoid the uncertainty of choosing the best time to predict nocturnal dipping and better identify the high risk patients with nocturnal hypertension. This leads to an overall improvement in the risk stratification for predicting cardiovascular deaths.